Changes to virus taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2019) - Walker, Peter J.; Siddell, Stuart G.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Dempsey, Donald M.; Dutilh, Bas E.; Harrach, Balázs; Harrison, Robert L.; Hendrickson, R. Curtis; Junglen, Sandra; Knowles, Nick J.; Kropinski, Andrew M.; et al. (Archives of virology, 2019)
This article reports the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in February 2019. Of note, in addition to seven new virus families, the ICTV has approved, by an absolute majority, the creation of the realm Riboviria , a likely monophyletic group encompassing all viruses with positive-strand, negative-strand and double-strand genomic RNA that use cognate RNA-directed RNA polymerases for replication.